Index of functionality of municipal electronic portals: access to health information (Research, Society and Development, 2021)
This study sought to investigate the extent to which health information has been made available to the population and the degree of functionality of the sites regarding access to the official websites of the municipalities that host the Regional Health Departments (DRS) of the State of São Paulo. To verify which sociodemographic, economic and health characteristics contribute to explain the functionality of municipal electronic portals. This is a descriptive-exploratory study, conducted in 17 cities in the state of São Paulo. The Functionality Index (IF) was determined by creating an instrument with 34 items divided into 4 dimensions. Subsequently, a Multiple Linear Regression was configured with the explanatory variables population, GDP, HDI-M, coverage of Primary Health Care, the Family Health Strategy and oral health to verify possible associations with the IF. The mean of the IF was 18.35; sd. 4.39; median 18; minimum 11 and maximum 29. The statistical model indicated that there was no statistically positive association between the IF and the explanatory variables. The availability of health information on municipal electronic portals showed low IF, in most of them. There was no positive relationship between the IF of the pages and their sociodemographic, economic and health characteristics.